A Synthesis of Practice-Oriented Literature in Gender and STEM (International Journal of Gender, Science and Technology, 2015)
Even as endorsement for the idea of "evidence-based practice" has become widespread, there has been little headway to find an empirical way to gauge whether models for best practice put forward in practice-oriented literature are&warranted. This research addressed questions about trends over time in both the quantity and quality of the evidence base of articles describing activities initiated to&promote the recruitment of retention of women and girls in STEM. Practice-oriented publications (n=142) were identified from a larger database (N=976) of articles with references to gender and STEM in the title or abstract. A six-point ordinal scale&was used to measure the quality of the foundational or evidence base of the articles. Between 1995 and 2009, the percentage of articles meeting the threshold&definition of being evidence-based grew from 43.8% in the first time period, to 49.3% in the second time period, and to 59.6% in the most recent time period. The relatively recent expansion of the digital infrastructure that supports the&dissemination of STEM-related publications, promises to minimize redundancy and to ensure that resources are invested in initiatives where there is evidence to&support its potential to be effective.